Risk Management Strategy Implementation for Business Plan at Material Handling Rental Services Startup LogisMe - Suryanto Suryanto; Rhian Indradewa; Edi Hamdi; Ketut Sunaryanto (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
PT. LogisMe Berkat Bersama (LBB) is a Limited Liability Company (PT) engaged in the business of providing Business-to-Business (B2B) warehousing and logistics solutions. LogisMe has the tagline "One Stop Logistics Solutions" with end-to-end solution coverage starting from the provision of warehousing and logistics operational equipment such as forklifts, material handling and cleaning equipment, provision of spare parts and technicians in order to meet the maintenance needs of these operational equipment, warehouse racking design, warehouse and logistics operational consultant services to the provision of a digital platform for monitoring units rented by customers in real-time. This document outlines the implementation of a risk management strategy for the business plan of LogisMe, a Material Handling Rental Services startup company. The framework adopted is based on the ISO 31000:2018 standard and focuses on integrating risk manage.  the report is returned to the risk mitigation supervisor to be checked that it has met the requirements and stored in the company's cloud repository, disseminated to all employees and company stakeholders. Monitoring is carried out to understand and prevent risks that occur as a strategy to gain a competitive advantage for the company.